Residual stress and subsurface damage in machined alumina and alumina/silicon carbide nanocomposite ceramics - Wu, H; Roberts, S; Derby, B (Elsevier, 2001)
We have used TEM and Hertzian indentation to study the interrelation between subsurface damage and residual stress introduced by grinding and diamond polishing surfaces of polycrystalline alumina and 5%SiC/alumina nanocomposites. In all cases a layer of high dislocation density was found near the surface. This varied in thickness from about 300 nm for alumina polished with 1 μm diamond grit to greater than 6 μm for a nanocomposite surface wheel-ground with 150 μm diamond grit. For a given finishing process the nanocomposites showed a greater depth of dislocation activity than alumina. In alumina, extensive basal twinning was found beneath the ground surfaces. Hertzian indentation data indicates a residual compressive stress of about 1500 MPa confined to the dislocation-containing region. Mechanisms for the enhanced dislocation activity in the nanocomposites are discussed.